LEARNING SOCIO-POLITICAL TERMS ON THE BASIS OF THEIR FIELDS OF MEANINGS - Torakhojaeva Adibakhan (Journals Park Publishing, 2022)
This article covers issues such as the systemic nature of the socio-political lexicon and the impact of national mentality as an extralinguistic factor on the lexical system.
Keywords: socio-political lexicon; OLM; linguistic field macrosystem